PENGARUH PENDIDIKAN KESEHATAN TERHADAP PENGETAHUAN TENTANG PERSONAL HYGIENE PADA ANAK USIA SEKOLAH DI SDN 206/IV KOTA JAMBI - Tina Yuli Fatmawati (Universitas Baiturrahim, 2018)
Health problems that often occur in elementary school age children are diseases related to child and environmental hygiene such as brushing teeth is good and right, the habit of washing hands with soap and personal hygiene. This studi aim to know to determine whether there is influence of health education to the knowledge of school-aged children about Personal Hygiene at SDN 206 / IV Kota Jambi. This research is a quantitative research using One Group pretest-posttest design. The research was carried out at SDN 206 / IV Kota Jambi in June 2017. The population is Students SDN 206 / IV Kota Jambi with a sample of 20 students. Data analysis using univariate and bivariate analysis with statistical test of T dependent. The result of this research is p-value = 0,00 <0,05 with difference of mean value -2.35. This indicates there is a significant influence between the knowledge of the respondents before and after being given health education.